Prenatal diagnosis of Fetal notochord syndrome: A case report and review of the literature - Abigail M. Ramseyer; Nafisa Dajani (Elsevier, 2020)
Introduction: Split notochord syndrome is a rare disorder characterized by fistula formation between the gastrointestinal tract and skin on the dorsum. Prenatal diagnosis is difficult and most cases are diagnosed postnatally. Clinical findings and diagnosis: A 29-year-old woman, gravida 3 para 2, was referred for fetal cystic chest mass on prenatal ultrasound for congenital pulmonary airway malformation (CPAM). Fetal magnetic resonance imaging (MRI) suggested foregut duplication, and this was confirmed on postnatal thoracotomy with mass excision. A spine dysraphism was suspected on prenatal ultrasound, but was not confirmed on fetal MRI at the time of the study. Neonatal MRI noted vertebral abnormalities, confirming split notochord syndrome. Retrospective examination of the fetal MRI images detected a dysraphism and confirmed the prenatal ultrasound findings. Outcome: At 17 months of life, the child had mild symptoms of neurogenic bowel, but was meeting all milestones without neurodevelopmental delays. We present a mild form of split notochord syndrome. Conclusion: Split notochord syndrome is difficult to diagnose prenatally and should be considered when a fetal cystic chest mass is found on ultrasound. Detailed vertebrae assessment may improve detection.